Determinants of trust - Lehmann-Waffenschmidt, M.; Leipold, K. (Nervenheilkunde, 2011)
Trust is important in social, economic and political life and therefore it is subject to research in various disciplines. This paper discusses recent research on trust from an economic perspective, especially about what determines and influences trust and trustworthiness. Trust is traditionally measured with the help of survey questions, but since the last two decades experimental games are primarily applied to measure actual trusting behavior. Summing up the results, trust is not only determined by belief about the trustworthiness of the partner, but is additionally based on different preference components such as risk preferences and social preferences. Especially the dislike of being betrayed by another person is an inhibitor of trust. Furthermore, this paper reviews differences in trusting behavior across cultures and concerning demographic variables. So far, however, the experimental evidence does not show a uniform picture. Indeed, individual differences in preferences and beliefs seem to provide an explanation for the observed differences in trust.
Keywords: Trust; trustworthiness; trust game; social preferences